Production of Aerial Biomass in Leucaena leucocephala (lam.) De Wit - Pathak, P. S.; Gupta, S. K.; Deb Roy, R. (Indian Forester, 1981)
Aerial biomass and coppice shoot growth observations of Leucaeua leucocephala, harvested at 3 and 4 years of age under farm forestry conditions have been presented in this paper. The mean annual increments after 3 and 4 years study show rising trend with maximum increment between the 3rd and 4th year. Under this system it can be possible to harvest fuel wood and forage upto 11.0 tons and 1.0 t/raw km respectively of dry matter on the 4th year. The coppice shoot growth in 1.5 years was found to be equal to the original 3 years growth of the trees thus indicating high coppice growth polentiality and forage yield in this plant.